Pengaruh Model Work Based Learning Terhadap Kemampuan Siswa Menerjemahkan Ayat Al Quran Pada Siswa Kelas Vii Mts Tarbiyah Waladiyah Pulau Banyak Tanjung Pura - Muamar Al Qaddri; Pera Ariyanti (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
The background of the problem regarding the learning methods applied at MTs Tarbiyah Waladiyah Pulau is that there is a conventional method by way of question and answer, giving assignments that are not effective,. Learning and teaching activities at MTs Tarbiyah Waladiyah Pulau Banyak have not implemented a cooperative learning model (Cooperative Learning), so that learning and teaching activities run monotonously. Methods of collecting data by means of observation, cognitive scale, and interviews. This data analysis technique goes through statistical stages in the form of Prerequisite Test, Data Linearity Test and Hypothesis Testing. The results of this study indicate that the work-based learning model cooperative learning is very suitable to be applied to Al-Qur'an Hadith subjects because in these learning activities by applying the Work-Based Learning model cooperative method students are actively involved, namely being active in asking questions, giving opinions, ideas and ideas so that students are not only objects of learning but students act as subjects of learning. There is an increase in the ability to translate the verses of the Qur'an Hadith based on the observation sheet obtained the percentage of student responses to cooperative learning obtained as much as 76.7%.